Web based pathology assessment in RTOG 98-04. Issue 9 (2nd July 2014) - Woodward, Wendy A; Sneige, Nour; Winter, Kathryn; Kuerer, Henry Mark; Hudis, Clifford; Rakovitch, Eileen; Smith, Barbara L; Pierce, Lori J; Germano, Isabelle; Pu, Anthony T; Walker, Eleanor M; Grisell, David Lawrence; et al.
Abstract : Aims: Radiation Therapy Oncology Group 98-04 sought to identify women with 'good risk' ductal carcinoma in situ (DCIS) who receive no significant benefit from radiation. Enrolment criteria excluded close or positive margins and grade 3 disease. To ensure reproducibility in identifying good risk pathology, an optional web based teaching tool was developed and a random sampling of 10% of submitted slides were reviewed by a central pathologist. Methods: Submitting pathologists were asked to use the web based teaching tool and submit an assessment of the tool along with the pathology specimen form and DCIS H&E stained slide. Per protocol pathology was centrally reviewed for 10% of the cases. Results: Of the 55 DCIS cases reviewed, three had close or positive margins and three were assessed to include grade 3 DCIS, therefore 95% of DCIS cases reviewed were correctly graded, and 89% reviewed were pathologically appropriate for enrolment. Regarding the teaching tool, 13% of DCIS cases included forms that indicated the website was used. One of these seven who used the website submitted DCIS of grade 3. Conclusions: Central review demonstrates high pathological concordance with enrolment eligibility, particularly with regard to accurate grading. The teaching tool appeared to be underused.